Estudo da técnica de ondas de tensão como instrumento de avaliação interna de árvores urbanas - Paduelli, Marcela Candian (2011)
Arborization is fundamental in urban spaces, due to the significant benefits it provides. To important issue to guarantee the adequacy of the role it plays is its maintenance. To this purpose, an application of preventive methods of diagnosis is recommended, allowing the evaluation of external and internal conditions of tress. Currently, the analysis of urban trees is subjectivity. For a complete and secure analysis, it is important to associate this visual external analysis to an internal analysis. This could be done by applying non-destructive techniques, wich allows an internal visualization of the tree through a tomographic image, without causing it any damage. Among the non-destructive techniques, that have applicability in the internal evaluation of urban trees, the technique of stress waves can be highlighted. Considering the great benefits that this technique can provide in the evaluation of urban trees, this research seeks to verify its scientific and technique viability, analyzing its reliability and also establishing some parameters of application. Studies with 12 trees of the Caesalpinea peltophoroides species (popularly known as Sibipiruna) have been carried out. The stress waves equipment was applied to sections of 50, 90 and 130 cm from the trees basis, generating tomographic images of these sections. Afterwards, the trees were cut at the level of these sections and, in order to compare these images, some pictures of them were made. The results show that the trees waves technique presents large applicability for internal evaluation of urban trees, achieving significant results. Also some parameters for the application of this technique were established. For instance, it is necessary to determinate the speed reference of waves propagation for the interpretation of tomographic images, as well as it is to determinate the best height of the assays section. The latter consisting on the height of the diameter to the chest height (DAP), where average density of the tree is representative.